Corneal Densitometry After Secondary Descemet Membrane Endothelial Keratoplasty. Issue 9 (September 2019) - Agha, Bishr; Dawson, Daniel G.; Kohnen, Thomas; Schmack, Ingo
Abstract : Purpose: To evaluate Scheimpflug corneal densitometry (CD) in patients undergoing secondary Descemet membrane endothelial keratoplasty (DMEK) after previous Descemet stripping automated endothelial keratoplasty or DMEK surgery. Methods: This was a retrospective institutional case series of 37 eyes of 37 patients. Two secondary DMEK groups, group 1A (n = 12 DMEK after Descemet stripping automated endothelial keratoplasty), group 1B (n = 11 repeat DMEK), and group 2 (n = 14 primary DMEK for Fuchs endothelial dystrophy) were formed. CD was obtained preoperatively, 1, 6, and 12 months postoperatively. In addition, corrected distance visual acuity, central corneal thickness, and endothelial cell density were assessed. Results: A significant decrease in grayscale units was observed in the 0- to 2-mm and 2- to 6-mm zones in all groups. For the 0- to 2-mm zone, values decreased from 49.11 ± 17.96 preoperatively to 22.87 ± 5.24 at 12 months (group 1A), from 45.16 ± 9.22 to 24.53 ± 14.21 (group 1B), and from 27.90 ± 8.30 to 16.64 ± 1.51 (group 2) ( P < 0.01). Group 2 showed significantly lower grayscale units than groups 1A and 1B preoperatively and 12 months postoperatively in the 0- to 2-mm and 2- to 6-mm zones. Significant correlations of CD and corrected distance visual acuity were found in groups 1A and 1B in the 0- to 2-mm zone at 12 months. There were no significant correlations between CD and central corneal thickness postoperatively. Conclusions: A decrease in CD could be demonstrated in secondary DMEK. Nevertheless, CD values remained significantly higher than in controls. This might point out the relevance of secondary corneal structural changes.